DNA damage caused by light-driven graphene oxide: a new mechanism. Issue 2 (20th January 2023) - Wang, Xujun; Zeng, Zihang; Yang, Tianhui; Zhang, Peng; Feng, Bo; Qing, Taiping
Abstract : The adsorption and cleavage behavior of DNA molecules by graphene oxide under UV irradiation were investigated in detail. It will provide novel insights into the potential environmental risk of graphene oxide in the aquatic environment. Abstract : Graphene oxide, a typical two-dimensional carbon-based nanomaterial, has been broadly applied in different industries because of its unique mechanical, electric, and thermal properties. These extensive applications will unavoidably release graphene oxide into the natural environment. In order to further evaluate the environmental behavior and environmental toxicity of graphene oxide, we systematically investigated the interaction mechanism between graphene oxide and DNA molecules, particularly the light-driven graphene oxide for DNA damage. Under light irradiation conditions, the graphene oxide has a strong cutting ability to DNA with different sequences. The cleavage behavior of DNA by graphene oxide mainly targets free DNA, which is similar to the degradation of non-adsorbed pollutants by nanomaterial catalysts. Both electron paramagnetic resonance and reactive oxygen species scavenging experiments indicated that 1 O2 and O2 ˙ − could be responsible for this DNA cleavage. In addition, the influence of several environmental factors (pH, metal ions, and biomolecules) on the cleavage reaction was investigated in detail. The results showed that these factors had little effect on the DNA-cutting reaction. This study provides novel insights into the potential environmental risk of graphene oxide.